A Myth of Kinship? Reinterpreting Lakota Conceptualization of Kin Relationships vis-à-vis 19th and 20th Century Historical Narratives - Kellie Hogue (Journal de la Société des Américanistes)
A Myth of Kinship? Reinterpreting Lakota Conceptualization of Kin Relationships vis-à-vis 19th and 20th Century Historical Narratives. Drawing upon the theoretical perspectives of Claude Lévi-Strauss, Raymond DeMallie, and Emmanuel Désveaux, this paper combines a structuralist approach with symbolic anthropology in an attempt to reinterpret historical categorization of Lakota kinship through an examination of the relationship between the Lakota and a pervasive representative of the non-material world in Lakota life, the bird. To begin this reinterpretation, I identify the existence of a special relationship between the Lakota and birds through a review of relevant myths. Then, I present qualitative data about the symbolic language of feathers found in the writings of 19th and 20th century Lakota people like Luther Standing Bear, White Bull, and Black Elk. Next, I explain how these symbols serve as intermediaries between the material and non-material cognitive worlds of the Lakota and birds. After considering the evidence presented, I suggest that 19th and 20th century Lakota notions of kinship were more complex than has been historically depicted because they took into consideration both human and non-human relationships. My goal is to provocatively prompt a reconsideration of the historical categorization of Lakota ideas of kinship to take into account the influence of non-human relations on social behavior and organization.